DISCOURSE ON INTERFAITH HARMONY IN THE CONSTRUCTION OF MULTICULTURALISM POLITICS - Haryanto, Wawan; Hasan, Hamsah (Jurnal Al-Dustur, 2023)
Building harmony among religious communities in a diverse nation requires sincere efforts, through multicultural politics. It can be understood that a diverse society can be integrated through the respect and acknowledgment of its diversity. This study is a qualitative descriptive research that focuses on literature review to explore relevant sources related to interfaith harmony through the lens of multicultural politics. Data are obtained from journals, books, and other research findings. In multicultural politics, policies supporting equal rights and protection for all groups are essential. Placing diversity as a positive force and avoiding discrimination will strengthen the foundation of an inclusive state. The key point of national awareness towards religious diversity is to create an environment where all citizens feel recognized, valued, and have equal opportunities. A positive attitude towards diversity not only reinforces national identity but also establishes a strong foundation for the development of a fair and inclusive society.From this research, it is hoped that the development of multicultural politics in creating an inclusive and harmonious environment for all religious communities in Indonesia can foster initiatives supporting interfaith harmony.